Neuroconnectivity analysis under mental workload and resting state conditions [Mental yüklenme ve dinlenim durumunda norobaǧlant?sallik analizi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
Brain activation can be observed by means of electrical and haemodynamic responses under the resting state condition. Several brain regions are synchronously activated to form functional brain networks during the resting state condition or while perforing a mental task. In the concept of this study, brain dynamics are measured using EEG and fMRI during rest and EEG is measured during a chess game which is used to increase the mental workload. fMRI measurements are analyzed using a seed based network computation technique while coherence computations are performed on EEG in order to deduce functional connectivity maps. EEG coherence maps are obtained after the solution of the inverse problem. So, connectivity is analyzed in the source domain. The cortex is parcellated with 84 node locations. The mental workload paradigm exhibited increased alpha band coherence in the prefrontal cortex. © 2017 IEEE.
Keywords: coherence; mental workload; resting state networks